(untitled) (Impact: Journal of Transformation, 2022)
The study examines Nigeria’s economic and security interests in relation to international organisations in the African political space. States within the global system employ the use of multilateral channels to achieve critical national interest objectives, and the manner with which each state uses the mechanism of international organisation in foreign policy-making process is different. This is borne out of endogenous features of a state. Thus, the current research attempts to appraise the place of international organisations in achieving economic and security interests of Nigeria in the African political system. The research is founded on the theory of national interest which assumes the centrality of state in international relations. The research therefore shows that Nigeria, most importantly in the West Africa sub-region, has been employing the mechanism of multilateralism in achieving security and economic interests. In conducting the research, the qualitative content analysis is used to study existing research materials like textbooks, journal articles, internet sources and documents.